The structure and electron energy loss near edge structure of tungsten oxide thin films prepared by pulsed cathodic arc deposition and plasma-assisted pulsed magnetron sputtering - Matthew R. Field; Dougal G. McCulloch; Sunnie H.N. Lim; André Anders; Vicki J. Keast; R.W. Burgess (Journal of Physics: Condensed Matter, 2008)
The microstructure and energy-loss near-edge structure (ELNES) of pulsed cathodic arc and pulsed magnetron sputtered WO3 thin films were investigated. It was found that the cathodic arc deposited material consisted of the α-WO3 phase with a high degree of crystallinity. In contrast, the magnetron sputtered material was highly disordered making it difficult to determine its phase. A self-consistent real space multiple scattering approach was used to calculate the NES of the various phases of WO3. Each phase was found to exhibit a unique NES allowing different phases of WO3 to be identified. The real space approach also allowed the origin of the main features in the NES to be investigated as the cluster size increased. The calculated NES for the room temperature γ-WO3 was found to compare well to previous X-ray absorption spectra and to NES obtained by full-potential band structure calculation.

Plasma biasing to control the growth conditions of diamond-like carbon - André Anders; Nitisak Pasaja; Sunnie H.N. Lim; Tim C. Petersen; Vicki J. Keast (Surface and Coatings Technology, 2007)
It is well known that the structure and properties of diamond-like carbon, and in particular the sp3/sp2 ratio, can be controlled by the energy of the condensing carbon ions or atoms. In many practical cases, the energy of ions arriving at the surface of the growing film is determined by the bias applied to the substrate. The bias causes a sheath to form between substrate and plasma in which the potential difference between plasma potential and surface potential drops. In this contribution, we demonstrate that the same results can be obtained with grounded substrates by shifting the plasma potential. This plasma biasing (as opposed to substrate biasing) is shown to work well with pulsed cathodic carbon arcs, resulting in tetrahedral amorphous carbon (ta-C) films that are comparable to the films obtained with the conventional substrate bias. To verify the plasma bias approach, ta-C films were deposited by both conventional and plasma bias and characterized by transmission electron microscopy (TEM) and electron energy loss spectrometry (EELS). Detailed data for comparison of these films are provided.
Keywords: Diamond-like carbon films; Electron energy loss spectroscopy; Plasma bias; Substrate bias; transmission electron microscopy